2016
DOI: 10.1186/s13643-016-0227-3
|View full text |Cite
|
Sign up to set email alerts
|

Insertion torque recordings for the diagnosis of contact between orthodontic mini-implants and dental roots: a systematic review

Abstract: BackgroundMost orthodontic mini-implants (OMIs) are inserted between dental roots. The prevalence of contacting these structures is high. Such contacts can cause permanent root damage and implant instability. Increased torque levels during implant insertion (the index test) could be a more accurate and immediate measure for diagnosing implant-root contact (the target condition) than radiographs (the reference standard) and could ultimately lead to a reduction or elimination of X-ray exposure. To address this i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…Insertion torque with root contact was proved to be higher than those without and in agreement with many studies [ 22 ]. One study showed that the average placement torques in contact cases were twice higher than those in noncontact cases [ 20 ].…”
Section: Complications During Insertionsupporting
confidence: 91%
“…Insertion torque with root contact was proved to be higher than those without and in agreement with many studies [ 22 ]. One study showed that the average placement torques in contact cases were twice higher than those in noncontact cases [ 20 ].…”
Section: Complications During Insertionsupporting
confidence: 91%
“…Therefore, torque levels should be recorded during the entire process of mini-implant insertion. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…It is known that insertion torque values do not result in predictions for long‐term stability, 17 and the present study found no association between baseline torque values and success. However, reference values may help to assess as a diagnostic test for root contact (a previously published study showed that miniscrews with root contact have different insertion torque values compared with those without) 33 and have less adverse effects than radiographic images 34 …”
Section: Discussionmentioning
confidence: 99%